Keys to success in business [videorecording] (Australia : Video Education Australasia, 1996)
"This video shows aspiring entrepreneurs ten principles for creating a solid, profitable company. Developing a realistic plan, seeking guidance from experienced mentors, building rapport with suppliers, and maintaing client relationships are a few of the subjects covered."--Container